DISKURSUS PEMBANGUNAN MANUSIADALAM PERDA SYARÎ’AH - Ahmad Muhlasul (Jurnal Sosiologi Reflektif, 2017)
Since its emergence, sharia nuanced regulations reap controversy. They are lately suspected as a part from project of International khilafah or even regarded as a part from project of radicalization laden with the smell of sectarian. There’s not little academic who regards that the existence of perda sharia as something that is contra productive and defies with the concept of nationalism intimated with Bhinneka Tunggal Ika (Unity in Diversity), also with the vision of global development, is the vision of human development followed by the whole countries in the world as a benchmark for development. This article is a summary from the whole research about the dimension of human development within perda sharia containing about the contestation between the vision of domestic and global policy. It is a literacy/library research using qualitative approach served and analyzed descriptively employing the theory of (development) Capabilitiy by Amartya Sen and Theory of Public Policy. The research is aimed to give a description about the relevance of Perda Sharia towards the concept of global development. The result of the research shows that there is conflict and tension between the vision of domestic and global policy. This thing is showed by the dominance of the incoherence between the content and context of perda sharia with the concept of human development and the latest models of policy developed by the UN.Sejak kelahirannya, Perda-Perda bernuansa Syarî’ah menuai kontroversi. Belakangan ia ditengarai sebagai bagian dari proyek khilafah internasional atau bahkan dianggap bagian dari proyek radikalisasi yang sarat dengan aroma sektarian. Tidak sedikit kalangan akademis yang menganggap bahwa keberadaan Perda Syarî’ah sebagai hal yang kontraproduktif dan bertentangan dengan konsep nasionalisme yang berbhinneka tunggal ika, serta bertentangan dengan visi pembangunan global, yaitu visi Pembangunan Manusia yang dianut oleh semua negara di dunia sebagai tolak ukur pembangunan.Artikel ini merupakan ringkasan dari keseluruhan penelitian tentang Dimensi Pembangunan Manusia dalam Perda Syarî’ah yang memuat tentang kontestasi antara visi kebijakan domestik dan global. Penelitian tersebut merupakan penelitian pustaka (literasi/library research) dengan pendekatan kualitatif yang disajikan dan dianalisa secara deskriptif menggunakan teori (Pembangunan) Kapabilitas Amartya Sen dan Teori Kebijakan Publik. Penelitian ditujukan untuk, memberikan deskripsi tentang relevansi Perda Syarî’ah terhadap Konsep Pembangunan global.Hasil penelitian menunjukkan adanya konflik dan ketegagan antara visi kebijakan domestik dan global. Hal itu ditunjukkan oleh dominannya inkoherensi antara kontent dan konteks Perda Syarî’ah dengan Konsep Pembangunan Manusia dan Model-Model Kebijakan terkini yang dikembangkan oleh PBB (UNDP).Key Words: Human Development, Sharia Law and Nationalism